In Situ Construction of Oriented Pt‐PANI Needle‐Like Nanoarrays‐Based Label‐Free Aptasensor for Ultrafast and Ultrasensitive Recognition of Cardiac Troponin I. Issue 24 (21st November 2021) - Zhang, Wei; Liu, Tao; Shan, Yuansheng; Hou, Bailing; Chu, Zhenyu; Gu, Xiaoping; Ma, Zhengliang; Jin, Wanqin
Abstract: Due to the short course and high mortality of acute myocardial infarction (AMI) which will cause irreversible myocardial necrosis to induce cardiac arrest, its early diagnosis within minutes is always a challenge in clinical emergency. In this work, an ultrafast and ultrasensitive aptasensor is designed to achieve quantitatively detection of cardiac troponin I (cTnI) which is proved as a highly specific and sensitive biomarker to AMI, and within only 4 min, the cTnI concentration can be accurately reported. This aptasensor is constructed via an in situ growth of the oriented Pt‐polyaniline (PANI) needle‐like nanoarrays providing both high electrocatalysis and abundant active sites as the signal magnifier and DNA carrier. A target‐induced strand release strategy is proposed to remarkably accelerate the recognition process of cTnI through the specific design of DNA stand for binding. The as‐prepared aptasensor can exhibit an ultrawide linear detection range of cTnI from 1 pg mL −1 to 100 ng mL −1 satisfying the clinical demand for AMI diagnosis, together with excellent selectivity among various biomarkers. Based on its fast recognition ability, this aptasensor presents a high accuracy in the practical detection of human serum to prove its promising ability in the early and on‐site diagnosis of AMI. Abstract : A label‐free aptasensor based on oriented Pt‐PANI needle‐like nanoarrays is designed to achieve the quantitative and accurate recognition of cTnI within only 4 min in the assay of human serum, relying on the abundant active probes on the nanoarrays to serve as the efficient DNA capture and signal magnifier.